Pengaruh Kualitas Pelayanan Terhadap Kepuasan Nasabah dan Loyalitas Nasabah Tabungan Britama Pada PT. Bank Rakyat Indonesia (Persero) Tbk Cabang Samarinda - Poppy Alvianolita Sanistasya (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2020)
This study aims to determine: (1) the effect of service quality on customer loyalty; (2) the effect of service quality on customer loyalty; (3) the effect of satisfaction on customer loyalty. The type of research (explanatory effect). Samples of 110 respondents of savings accounts in BRI branch Samarinda. This study uses survey methode and data collection methods using questionnaires. Analysis of data used path analysis. Results of the path analysis can be seen that: (1) service quality variable have a significant effect on customer satisfaction variable; (2) service quality variable have a significant influence on customer loyalty variable; (3) customer satisfaction variable do not have a significant effect on customer loyalty variable.